2019
DOI: 10.1016/j.msard.2019.07.028
|View full text |Cite
|
Sign up to set email alerts
|

Minimally important difference of the fatigue severity scale and modified fatigue impact scale in people with multiple sclerosis

Abstract: Background: Fatigue is a common and debilitating symptom of Multiple Sclerosis (MS); however, it is unknown what constitutes a clinically significant change in fatigue. Establishing the minimally important difference (MID) of fatigue outcome measures can inform the interpretation of changes in fatigue by estimating the level of change that is considered clinically relevant. Aim: Determine the MID for the Fatigue Severity Scale (FSS) and Modified Fatigue Impact Scale (MFIS) in people with MS. Methods: This cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
84
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(84 citation statements)
references
References 36 publications
(21 reference statements)
0
84
0
Order By: Relevance
“…A recent paper reported the minimal clinically important difference (MCID) in the FSS and MFIS scores in patients with MS to be 0.45 and 4 points, respectively. 32 Another study reported the MCID in the MFIS score in patients with Parkinson’s disease was 13.8. 33 The change from the baseline in both FSS (at 1 week) and MFIS (at day 28) in our study was greater than these minimally important differences reported in the literature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent paper reported the minimal clinically important difference (MCID) in the FSS and MFIS scores in patients with MS to be 0.45 and 4 points, respectively. 32 Another study reported the MCID in the MFIS score in patients with Parkinson’s disease was 13.8. 33 The change from the baseline in both FSS (at 1 week) and MFIS (at day 28) in our study was greater than these minimally important differences reported in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…FSS and MFIS are commonly used fatigue measures in MS studies, have been extensively validated, 31 and in the case of MFIS, has been recommended as the instrument of choice for the evaluation of fatigue in MS. 7 MFIS measures the impact of fatigue in multiple domains, including physical, cognitive, and psychosocial. Observing a major therapeutic effect of ketamine on the MFIS and its subdomains at day 28 32 Another study reported the MCID in the MFIS score in patients with Parkinson's disease was 13.8. 33 The change from the baseline in both FSS (at 1 week) and MFIS (at day 28) in our study was greater than these minimally important differences reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…In the different studies were used separate questionnaires to assess the problems of patients with MS, for example measurement of fatigue through FSS scale (29), stress, anxiety and depression through DSAA 21 scale (30), physical problems using several questionnaires (12, 31 -32). The MSHPQ scale evaluate all of the health problems including physical, psychological, emotional, family and socio -economic problems in MS patients in a single questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…79 The MFIS score ranges from 0 to 84, with higher scores indicating greater fatigue impact and a change ranging from 3.86 to 8.11 being clinically relevant. 80 All of these questionnaires will be completed at baseline, after 24 weeks, after 48 weeks, and again at 1-year follow-up.…”
Section: Patient-reported Outcome Measuresmentioning
confidence: 99%